Research on Real Time Data Processing and Application of Urban Rail Train - ZENG Gaoping; WANG Lei (Kongzhi Yu Xinxi Jishu)
With the rapid development of urban rail transit in China, the demand for safe and intelligent operation is growing. According to the actual operation needs of urban rail train, this paper builds a real-time streaming data processing architecture for intelligent operation and maintenance adopting technologies such as big data, mobile internet, internet of things, and micro-services. This paper mainly expounds a portable, scalable and efficient processing method base on train real-time data, which realizes the functions of rapid data verification, analysis, storage, sharing, push, etc., and supports the application system to realize real-time train monitoring and emergency response and disposal guidance, train daily inspection items self-inspection and other functions. The proposed system mainly includes two parts: data platform and application platform. The data platform completes rapid processing of real-time data stream sent by the onboard device with the help of high-concurrency asynchronous IO framework, message queue, stream computing, storage engine and other big data processing components; efficient real-time interaction and flexible application of real-time data are realized with database, active data push and other technologies. The application platform uses real-time data of train to realize train-related demand functions, and effectively converts the data into actual business form, thereby improves the ability of personnel to perceive the running status of vehicle, reducing workload of artificial maintenance and operation, and ensuring the train high-quality operations.